2014
DOI: 10.1371/journal.pone.0091061
|View full text |Cite
|
Sign up to set email alerts
|

Serum BDNF Levels in Relation to Illness Severity, Suicide Attempts, and Central Serotonin Activity in Patients with Major Depressive Disorder: A Pilot Study

Abstract: The aim of this study was to test the hypothesis that serum levels of brain-derived neurotrophic factor (BDNF) are correlated with the loudness dependence of auditory evoked potentials (LDAEP). The question of whether there is a difference in BDNF levels between depressive patients according to their illness severity, history of suicide attempts, and central serotonin activity was also addressed. A sample of 51 patients who met the criteria for major depressive disorder following diagnosis using axis I of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 60 publications
1
24
1
1
Order By: Relevance
“…A possible interpretation of these results is that impulsiveness itself is associated with greater BDNF production, and this is consistent with results from a study conducted by Park et al (2014) in which BDNF levels positively correlated with impulsiveness in a sample of major depressed patients. This hypothesis is also in line with other studies in which high BDNF serum levels were associated with psychiatric syndromes characterized by high levels of impulsiveness, such as severe Gambling Disorder (Angelucci et al, 2013), Anorexia Nervosa (Mercader et al, 2007), ecstasy use , ADHD (Shim et al, 2008), personality disorders with high impulsiveness (Minelli et al, 2011;Archer et al, 2012) and novel psychoactive substance use , a popular phenomenon among adolescents and young adults with high levels of impulsiveness and binge habits .…”
Section: Discussionsupporting
confidence: 89%
“…A possible interpretation of these results is that impulsiveness itself is associated with greater BDNF production, and this is consistent with results from a study conducted by Park et al (2014) in which BDNF levels positively correlated with impulsiveness in a sample of major depressed patients. This hypothesis is also in line with other studies in which high BDNF serum levels were associated with psychiatric syndromes characterized by high levels of impulsiveness, such as severe Gambling Disorder (Angelucci et al, 2013), Anorexia Nervosa (Mercader et al, 2007), ecstasy use , ADHD (Shim et al, 2008), personality disorders with high impulsiveness (Minelli et al, 2011;Archer et al, 2012) and novel psychoactive substance use , a popular phenomenon among adolescents and young adults with high levels of impulsiveness and binge habits .…”
Section: Discussionsupporting
confidence: 89%
“…The combined data of 16 studies (before the exclusion criteria were applied) are presented in Tables and . In the end only nine studies fulfilled our inclusion criteria; these studies were performed in Korea (Kim et al., ; Lee & Kim, ; Lee, Kim, Park, & Kim, ; Park, Lee, Um, & Kim, ); Taiwan (Huang & Lee, ); Turkey (Deveci, Aydemir, Taskin, Taneli, & Esen‐Danaci, ); China (Liang, Zhang, Hong‐Ya, & Lv, ); Canada (Eisen et al., ), and Brazil (Pinheiro et al., ). As a result, in this meta‐analysis we included 246 cases and 601 controls overall, which were distributed in 80 cases and 145 controls for the meta‐analysis of plasma samples; 166 cases and 456 control for the meta‐analysis of serum samples.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we conducted a meta‐analysis to assess whether BDNF levels in serum were lower in cases than in controls. In this analysis the sum of samples consisted of six studies that evaluated the association between BDNF levels in serum for cases with suicide attempt and controls (Deveci et al., ; Eisen et al., ; Huang & Lee, ; Liang et al., ; Park et al., ; Pinheiro et al., ). The analysis did not show statistical difference in serum BDNF levels between cases and control groups ( d = −0.51, 95% CI −1.06 to 0.33 ng/ml, I 2 = 83.79, p ( Q ) < .001 (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Considerable evidence has pointed to a dysregulation of neurotrophic processes in relation to depressive disorders [10,11,[29][30][31][32]. A recent meta-analysis indicated that the Met allele of the BDNF Val66Met polymorphism moderated the relationship between stressful life events and the development of depression [33].…”
Section: Discussionmentioning
confidence: 99%